Implementation of Project Based Learning Method in Developing Cognitive Abilities of Children Aged 5-6 Years Through Loose Parts Media - Aulia, Maya Putri; Sudarti, Sudarti; Zar'in, Firdaus (CV. Pusdikra Mitra Jaya, 2024)
This study aims to explore the implementation of Project Based learning (PBL) method in developing cognitive abilities of children aged 5-6 years through loose parts media. The research used a descriptive qualitative approach with a focus on observing the implementation of learning activities at 'Aisyiyah Bustanul Athfal 3 Kindergarten, Southeast Pontianak. Data were obtained through observation, interviews, and document analysis. The results showed that the PBL method applied through loose parts media was effective in developing cognitive abilities of children aged 5-6 years. Careful planning, the active role of teachers in supporting activities, and the use of interesting media are important factors in the successful implementation of this method. In addition, the results also showed that children showed progress in problem solving, logical thinking and symbolic thinking through active participation in learning activities. The findings make an important contribution to the understanding of the use of the PBL method and loose parts media in the context of early childhood education and provide practical guidance for educators to improve the quality of learning in early childhood education institutions.